The impact of health system governance and policy processes on health services in Iraqi Kurdistan - Khoshnaw Hiro; Tawfik-Shukor Ali (BMC, 2010)
Abstract Background Relative to the amount of global attention and media coverage since the first and second Gulf Wars, very little has been published in the health services research literature regarding the state of health services in Iraq, and particularly on the semi-autonomous region of Kurdistan. Building on findings from a field visit, this paper describes the state of health services in Kurdistan, analyzes their underlying governance structures and policy processes, and their overall impact on the quality, accessibility and cost of the health system, while stressing the importance of reinvesting in public health and community-based primary care. Discussion Very little validated, research-based data exists relating to the state of population health and health services in Kurdistan. What little evidence exists, points to a region experiencing an epidemiological polarization, with different segments of the population experiencing rapidly-diverging rates of morbidity and mortality related to different etiological patterns of communicable, non-communicable, acute and chronic illness and disease. Simply put, the rural poor suffer from malnutrition and cholera, while the urban middle and upper classes deal with issues of obesity and Type 2 diabetes. The inequity is exacerbated by a poorly governed, fragmented, unregulated, specialized and heavily privatized system, that not only leads to poor quality of care and catastrophic health expenditures, but also threatens the economic and political stability of the region. There is an urgent need to revisit and clearly define the core values and goals of a future health system, and to develop an inclusive governance and policy framework for change, towards a more equitable and effective primary care-based health system, with attention to broader social determinants of health and salutogenesis. Summary This paper not only frames the situation in Kurdistan in terms of a human rights or special political issue of a minority population, but provides important generalizable lessons for other constituencies, highlighting the need for political action before effective public health policies can be implemented - as embodied by Rudolf Virchow, the father of European public health and pathology, in his famous quote "politics is nothing but medicine at a larger scale".